A relação homem/natureza: a destruição da natureza na sociabilidade capitalista - Santos, Ana Claudia do Nascimento (2014)
The actual work accomplish an theoretical reflection about of devastation of Nature, above all in capitalistic sociability. This have how objective to search into the causal links that denote the essence of such problematic. For thus, we accomplish, beginning, an analysis of ontological foundations of relation man/nature. We take how theoretical basis the studies of Friedrich Engels, that consider the work an central class in passage of monkey by the man. In studies of Karl Marx we are be able to find out that the interchange organic of man with the nature is mediated by work and their essential elements. With the objective we learned the category work in their foundations, we obtain in theoretical entrance of György Lukács the ontological centrality of work in formation of social creature, defend for Lukács to depart of Marx. We search also how develop itself the relation man/nature in pre-capitalistics societies and how occur the process of dissociation among the direct producer and their middle of production, with basis in analysis accomplished by Karl Marx, by the search the passage of feudalistic society for capitalist society. From that by, we find out that the devastation of nature that actual occur to arise from of process of formation of capitalistic sociability and has been deepened on measure that expand itself the destructive logic of capitalistic production. For that, base us in analysis of István Mészáros. By depart of search accomplished, we investigate that the devastation of nature has origin by depart of instant in that the man pass by to explore the nature for the his survival and perpetuate itself till the present time. The resolution from that problematic indicate for the instauration of an new shape of sociability that base itself in equivalent access by the goods and services, well as in appropriation collective of social wealth producted.